Perkembangan Terkini Riset Kualitas Laporan Keuangan - Ratih Purwasih (SAFE-Network, 2023)
This study aims to provide a broader picture of research on the quality of financial reports and what factors influence the quality of financial reports through a literature study in research in the field of accounting in national journals (Sinta 2) and international journals (Emerald and ProQuest) within the period 2013-2021 time. The keywords used in the search are the quality of financial statements (financial statement quality) and the quality of financial reporting (financial reporting quality). Found as many as 37 research articles that are relevant to the specified topic. This study identifies the main directions of research on the quality of financial reports in the period 2013-2021 and discusses several important aspects of research such as research methodology, theory used, research sector and others. In the end, it can be concluded from this study regarding the development of research on the quality of financial reports so that it can provide input for further research.